Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Script di Kelas V Sekolah Dasar - Majid, M. Thoriq; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This study attempts to describe the increase in the learning outcomes of fifth-grade students at SD Negeri 02 Sariak Laweh, Lima Puluh Kota District by using the Script Type Cooperative Learning approach. Classroom action research (CAR) is a type of research that combines qualitative and quantitative methods. The subjects of this study were teachers and students of class V, totalling 18 people. There are 4 stages, namely planning, implementation, observation, and reflection consisting of two research cycles. Test sheets and non-test sheets are tools used to collect data. The results of the analysis show an increase: a) RPP in cycle I averaged 85% (B), increased to 94.44% (SB) in cycle II, b) Implementation of learning on the teacher aspect increased from 84.25% (B) in cycle I to 93.75% (SB) in cycle II; and in the student aspect increased from 84.25% (B) to 93.75% (SB) in cycle two, c) The value of student learning outcomes in cycle I was 83.35 (B), increased to 91 (B) in cycle II. In fifth-grade students of SD Negeri 02 Sariak Laweh, Lima Puluh Kota District, it can be determined that the script-type cooperative model becomes more intensive so as to produce better learning outcomes for the integrated thematic learning process.